Apology to the ecosystem: A Stylistic Analysis of Linda Hogan’s "Song for the Turtles in the Gulf" - Ansar, Mohammed; Meiling, Zuo (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
This paper conducts a stylistic analysis of Linda Hogan's eco-friendly poem “Song for the Turtles in the Gulf,” examining its ecological concerns through the exploration of tone, symbols, images, personification, and intertextuality. Against the background of the 2010 BP oil spill, this poem issues a reflection on the disastrous impact of human endeavouring and development on the environment and, more specifically, sea turtles. This paper provides an analysis of how Hogan uses literary elements to appeal to the emotions and raise awareness about the environment to show that the poem challenges contemplation and rightful action in view of the raging environmental degradation. The analysis emphasizes the turtle as a symbol of vulnerability and environmental degradation. Moreover, the paper also analyzes some selected techniques of Hogan, such as personification and intertextuality, which make the reader think more about the ecological context and humanity’s critical position on it. In conclusion, this research benefits the field of ecocriticism by showing that close reading of literature enriches the moral and affective calls of environmental literature.